Menyelisik Makna Kata Khabīth dalam Al-Qur’an dengan Pendekatan Semantik Toshihiko Izutsu - Saputra, Ali Thaufan Dwi; Taufiquzein, Ahmad Ilyas (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2022)
The main concern of the author in this study is to examine the word khabīth which is found in various verses in the Qur’an. In studying the word, the author uses syntagmatic and paradigmatic analysis contained in the semantic theory by Toshihiko Izutsu. This research uses the type of library research. The type of research in terms of the implementation perspective in this research is descriptive research. This is an attempt to describe the object of study that is studied in depth. The main question to be answered in this research is how is the world view of the Qur’an towards the word Khabīth from a semantic perspective? The findings in this study indicate that the word Khabīth has the basic meaning of an evil. But based on syntagmatic and paradigmatic analysis, these basic meanings become various meanings, each of which has a relationship or relation. Another finding in this study is that the meaning of the word Khabīth has “shifted without losing basic meaning” since pre-Islam and after the revelation of Qur’an.